Self-Financing of Traditional and R&D Investments: Evidence from Italian SMEs - Paola Brighi; Roberto Patuelli; Giuseppe Torluccio (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Self-financing has often been seen as an important source for research-and-development (R&D) funding. However, an in-depth comparison between the determinants of self-financing in the case of traditional investments versus those in R&D has not been provided yet. We use a comprehensive data set of Italian manufacturing firms to investigate this issue. We analyse the role of a wide number of financial variables in driving the rate of self-financing of firms, in both traditional and R&D investments, and we focus on public subsidies and firm size as critical factors explaining heterogeneity. First, we perform logit and logistic regressions separately for traditional and R&D self-financing, finding that they are positively correlated, and that the availability of public subsidies reduces self-financing. Subsequent poolability tests show that public subsidies and firm size are crucial discriminating factors for self-financing behaviour. Our main finding is that, in the absence of public subsidies, no internal or external market variable is able to explain the firms' financing decisions. Furthermore, our analyses generally show that credit constraints and banking relationship variables are relevant in determining traditional investment self-financing, while no clear statistical evidence is found in the R&D case. Credit rationing is not significant for R&D selffinancing, which may be explained by rationed firms being left out of our sample.
Keywords: D45; D82; E51; G21; G32; O32; 330